Examining the Leadership Styles of Different Branch Teachers - Utku DURAN; Alparslan ÜNVEREN (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi)
The present study seeks to ascertain the leadership styles exhibited among various subject teachers and analyze them in relation to different variables. A total of 113 male and 165 female teachers, specializing in physical education, Turkish, science, and classroom teaching, took part in the study. A personal information form was used to collect various demographic and professional characteristics of the participants, including age, body mass index (BMI), marital status, place of residence, branch, professional year, professional title, and managerial status. The researchers utilized the "Teacher Leadership Style Scale" created by Deniz and Hasançebioğlu (2003) to assess the leadership styles of the participants. Aside from conducting percentage and frequency analyses, the data analysis also involved the use of independent sample t-test and one-way analysis of variance test. The research findings indicate that teachers, regardless of their field, exhibited an autocratic leadership style, while classroom teachers demonstrated a democratic leadership style. A notable disparity was observed between the leadership styles of teachers and the demographic and professional factors that were analyzed, specifically in relation to the professional title variable.